Analysis of Production and Income from Mixed Cropping Systems between Cocoa and Durian in Matanggorai Village, Padangguni District, Konawe Regency - Fadli, Afdal; Saediman; Zani, Munirwan (International Journal of Technology and Education Research, 2025)
This study aims to find out 1) Production of mixed agricultural system between cocoa and durian and 2) Income of mixed agricultural system between cocoa and durian in Matanggorai Village, TPadangguni District, Konawe Regency. The research was conducted in Matanggorai Village, Padangguni District, Konawe Regency, Southeast Sulawesi Province. This research starts from March to June 2024. The population in this study is all farmers who apply the Mixed Cocoa and Durian agricultural system in Matanggorai Village, Padangguni District, Konawe Regency as many as 20 people. The sample determination technique used in this study is using the census sampling method. The census sampling technique is a technique characterized by taking the entire population as a research sample, so that the sample used in this study is 20 people. The data analysis used is revenue analysis, production analysis and Joint Cost. The results of the study showed that the production of Mixed Farming Between Cocoa and Durian in Matanggorai Village, Padangguni District reached Rp 1,639,092.08/season. This productivity reflects the efforts of farmers in implementing efficient cultivation techniques and the use of appropriate inputs to support farming. The average income of farmers who apply the Mixed Agriculture system between cocoa and durian in Matanggorai Village is Rp 20,4299,696.9/season.This sizable net income shows the effectiveness and efficiency in farming, as well as the high profitability potential of the implementation of the cocoa and durian mixed agriculture system in this region